CITADEL: Computational Investigation of the Topographical and Architectural Designs in an Evolving Landscape (research data) - Pattee, Aaron (Universität, 2023)
The data found in this repository contain the basis for the historical, architectural, and geo-spatial analyses discussed in the dissertation entitled: CITADEL – Computation Investigation of the Topographical and Architectural Designs in an Evolving Landscape. These data include the following categories. 1. Photogrammetric Data: all photos, calibration information, and Agisoft Metashape projects for the four sites. All post-processed 3D models of the photogrammetric process and their associated perspectives from which orthophotos were generated for the construction research. 2. Laserscan Data: all raw data and calibration information pertaining the four sites as recorded by the Riegl VZ-400 laser scanner, and all post-processed 3D models of the sites. 3. GIS Data: all historical maps that were geo-referenced in the project, the entire QGIS project file with all associated layers, all raster and vector data saved as individual files, and all shapefiles saved as individual files. 4. Graph Database: all spreadsheets containing the base information drawn from the charters provided by online and analog sources. The entire Cypher Script as well as instruction for importing the data into Neo4j. The rubric outlining how the status and administration positions of the individuals in the charters were ranked relative to one another. The cognitive development of the database’s structure represented by graph schemas over time. 5. Architectural Plans: the roombook outlining every wall, architectural element, and building phase of the four sites. All 76 architectural plans of the construction research using orthophotos of the photogrammetric models.